2020
DOI: 10.1182/bloodadvances.2020002731
|View full text |Cite
|
Sign up to set email alerts
|

The prospective Hemophilia Inhibitor PUP Study reveals distinct antibody signatures prior to FVIII inhibitor development

Abstract: Preventing factor VIII (FVIII) inhibitors following replacement therapies with FVIII products in patients with hemophilia A remains an unmet medical need. Better understanding of the early events of evolving FVIII inhibitors is essential for risk identification and the design of novel strategies to prevent inhibitor development. The Hemophilia Inhibitor Previously Untreated Patients (PUPs) Study (HIPS; www.clinicaltrials.gov #NCT01652027) is the first prospective cohort study to evaluate comprehensive changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…Detection of IgG1 antibodies in hemophilia A inhibitors samples by FLI demonstrated that IgG1 antibodies preceded a positive inhibitor titer in five of seven patients who ultimately developed inhibitors, but IgG4 antibodies were detected in patients with negative inhibitor titers and those without an inhibitor history 11,18 . Similarly, the prospective observational Hemophilia Inhibitor PUP study evaluating biomarkers in inhibitor development among previously untreated patients with severe hemophilia A detected high‐affinity IgG1 antibodies before detection of an inhibitor along with high‐affinity IgG3 and IgG4 antibodies; however, IgG4 was not detected in subjects with LTIs, FVIII‐specific non‐neutralizing antibodies, or subjects without FVIII inhibitors or antibodies 21 . A limitation of this current study is the lack of routine evaluation of FVIII antibody profiling over time prior to patients switching to emicizumab for comparison.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Detection of IgG1 antibodies in hemophilia A inhibitors samples by FLI demonstrated that IgG1 antibodies preceded a positive inhibitor titer in five of seven patients who ultimately developed inhibitors, but IgG4 antibodies were detected in patients with negative inhibitor titers and those without an inhibitor history 11,18 . Similarly, the prospective observational Hemophilia Inhibitor PUP study evaluating biomarkers in inhibitor development among previously untreated patients with severe hemophilia A detected high‐affinity IgG1 antibodies before detection of an inhibitor along with high‐affinity IgG3 and IgG4 antibodies; however, IgG4 was not detected in subjects with LTIs, FVIII‐specific non‐neutralizing antibodies, or subjects without FVIII inhibitors or antibodies 21 . A limitation of this current study is the lack of routine evaluation of FVIII antibody profiling over time prior to patients switching to emicizumab for comparison.…”
Section: Resultsmentioning
confidence: 97%
“…affinity IgG3 and IgG4 antibodies; however, IgG4 was not detected in subjects with LTIs, FVIII-specific non-neutralizing antibodies, or subjects without FVIII inhibitors or antibodies 21. A limitation of this current study is the lack of routine evaluation of FVIII antibody profiling over time prior to patients switching to emicizumab for comparison.TA B L E 2…”
mentioning
confidence: 83%
“…Our study does have some limitations. First, there are likely differences in the established, longer immune response seen in adults versus pediatric inhibitor patients whose immune responses may still be evolving, as noted in the HIPS study ( 34 ). However, the continued elevation of BAFF in the adult HA inhibitor population (which otherwise should fall) supports the hypothesis that BAFF modulates the FVIII immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Long-lived PCs (LLPCs) ultimately settle in the bone marrow (BM), sustaining the humoral response for extended periods. In humans, the antibody response against FVIII consists of both neutralizing (high affinity, IgG 4 ) and nonneutralizing (low affinity, IgG 1 ) antibodies ( 34 ), likely from B cell receptor (BCR) rearrangement driving affinity maturation. In mice, it is generally thought that IgG 1 most closely mimics human IgG 4 ( 35 ), but inhibitory α-FVIII antibodies of many subclasses have been described ( 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence of the FVIII inhibitor was accompanied by an increase in levels of both anti-FVIII IgG1 and IgG4, which parallels the situation in previously untreated patients who develop FVIII inhibitors during FVIII prophylaxis. 7 Interestingly, in our patient, IgG1 was very low, but still detectable, before emicizumab initiation, while the inhibitor was undetectable for several years before. This may explain the difference with patients reported by Batsuli et al who remained negative in both Bethesda and ELISA for the IgG1 isotype.…”
Section: Reappearance Of the Inhibitor Was Not Associated With Any Notable Clinical Eventsmentioning
confidence: 50%